The Implementation of Teacher Strategies in Maintaining Sundanese Culture in the Senior High School Region I West Java - Puspitasari, Yola; Zid, Muhammad; Hardi, Ode Sofyan (Indonesia University of Education, 2021)
This research aims to analyze the implementation of teacher strategies in maintaining Sundanese Culture in West Java, at Senior High Schools in Region I West Java. The research method used was descriptive-qualitative with literature study. Data collection techniques were done through interviews, documentation, and examining secondary data as complementary data. The results showed that territory that were further away from the Priangan/Bandung area such as Depok City, and parts of Bogor Regency which bordered by Banten and Depok, has cultural acculturation and it was difficult to maintain Sundanese language, so that this region places great emphasis on Sundanese arts and traditional clothes. To instill a love â€œnyaahâ€ or love of Sundanese culture, namely by implementing Sundanese art activity program strategies and competitions on Sundanese culture in schools by adjusting the language used in the area, namely Indonesian with the Betawinese dialect. Meanwhile for territory of closer Priangan/Bandung like the Sukabumi City, Bogor City, Cianjur Regency, Sukabumi Regency, and parts of Bogor Regency which border Cianjur-Sukabumi, there is no difficulty that the maintenance of Sundanese culture, because the majority of students in this region is the original Sundanese people. Yet these areas implement strategy in the use of language in accordance undak-usuk or origin of Sundanese language through a lesson and outside of a lesson, and focused on aspects art and Sundanese traditional clothes, with an implement strategy through activity program pasanggirikasundaan (competition on Sundanese) and art Sundanese at school.